Entorno familiar y rendimiento escolar de los alumnos con habilidades diferentes del área SAANEE - CEBE Chepén, 2021 - Rodríguez Tafur, Gabriela Paola (2023)
The purpose of this thesis was to analyze the influence of the family environment on the school performance of students with different skills from the SAANE area of CEBE Chepén, 2021. The type of applied research has been considered, based on an explanatory design, and the sample consisted of 71 students with different skills from the SAANE area of CEBE Chepén, with whom we worked applying the methods and techniques of quantitative research: Statistical method and as a technique to survey, and qualitative research: Inductive method - deductive; and as techniques direct observation and interview. The results obtained show that the inadequate family environment and the poor communication and latent conflicts that arise in their family environment affect the school performance of students with skills other than SAANE - CEBE Chepén. These data reflect the primary aspects of parents' lack of commitment to the educational process of their children, which is so important for successful school performance. There is a large percentage of parents who do not devote time to their children, and children who make known the terrible relationship with their parents, which directly influences the performance of students. Finally, as social workers we project that this study is a starting point to persuade parents and responsible institutions, that concerted efforts should be made to implement the social inclusion policy for all disabled persons in order to improve their quality of life.